2020
DOI: 10.3390/s20226632
|View full text |Cite
|
Sign up to set email alerts
|

Application of Near-Infrared Spectroscopy to Investigate Some Endogenic Properties of Pleurotus ostreatus Cultivars

Abstract: Fourteen different Pleurotus ostreatus cultivars (Po_1–Po_14) were tested for free amino acid content (fAA), total polyphenol content (TPC), and antioxidant capacity (Ferric Reducing Ability of Plasma—FRAP) to select the cultivars with the most favorable traits. Automatic amino acid analyzer (fAA) and spectrophotometric assay (TPC, FRAP) results as well as Fourier-transform near infrared (FT-NIR) spectra were evaluated with different chemometric methods (Kruskal–Wallis test, Principal Component Analysis—PCA, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Typically, amino acids have been reported as antioxidant substances. Fodor et al reported that free amino acids contributed to FRAP [ 50 ]. Cit has the characteristics of a hydroxyl radical scavenger [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Typically, amino acids have been reported as antioxidant substances. Fodor et al reported that free amino acids contributed to FRAP [ 50 ]. Cit has the characteristics of a hydroxyl radical scavenger [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of POSF, the values for the remaining amino acids were in agreement with previously reported in all cases except Ser (0.39–0.59 g/100 g) and Leu (0.39–0.67 g/100 g), in which the results obtained in this study were lower than the 0.91 and 1.01 g/100 g, respectively, described by Dabbour et al [ 64 ]. Differences in amino acid content could be due to strain differences [ 65 ]. It is important to note that the samples comprised all essential amino acids; this high protein quality could make these flours a suitable ingredient for the enrichment of plant-based foods.…”
Section: Resultsmentioning
confidence: 99%
“…These spectrometers, which are miniature versions of vibrational spectroscopy equipment, have made it possible for the food industry to do on-site and real-time evaluations of food quality and food production processes. They have been used for authentication and detection of adulterants in several foods [ 19 , 20 , 21 ], food product development [ 22 , 23 ], and geographical discrimination of food [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%